A 4 year observation of gastrointestinal nematode egg counts, nemabiomes and the benzimidazole resistance genotypes of Teladorsagia circumcincta on a Scottish sheep farm. Issue 5 (April 2021) - Evans, M.J.; Chaudhry, U.N.; Costa-Júnior, L.M.; Hamer, K.; Leeson, S.R.; Sargison, N.D.
Graphical abstract: Highlights: Metabarcoded sequencing was used to determined species composition (nemabiome) of gastrointestinal nematode (GIN) larvae. Deep amplicon sequencing determined proportions of benzimidazole (BZ)-resistant SNPs in Teladorsagia circumcincta. Nemabiomes varied with time and between ewes and lambs, possibly associated with weather. The F200Y BZ resistance mutation was close to genetic fixation in T. circumcincta. There was no genetic evidence of reversion to BZ anthelmintic susceptibility. Abstract: Anthelmintic resistance threatens the sustainability of sheep production globally. Advice regarding strategies to reduce the development of anthelmintic resistance incorporates the outcomes of modelling exercises. Further understanding of gastrointestinal nematode species diversity, and population dynamics and genetics (which may vary between species) is required to refine these models; and field studies combining faecal egg outputs, species composition and resistance genetics are needed to calibrate them. In this study, faecal samples were taken from ewes and lambs on a commercial farm in south-eastern Scotland at approximately 3 t-4 week intervals between spring and autumn over a period of 4 years. Faecal egg counts were performed on these samples, and L3 were collected from pooled coprocultures. Deep amplicon sequencing was used to determine both the species composition of these L3 and the proportions of benzimidazole-resistant single nucleotide polymorphisms in the isotype-1 β-tubulin locus of the predominant species, Teladorsagia circumcincta L3 . Despite consistent management throughout the study, the results show variation in gastrointestinal nematode species composition with time and between age groups, that was potentially associated with weather conditions. The F200Y benzimidazole resistance mutation is close to genetic fixation in the T. circumcincta population on this farm. There was no evidence of variation in isotype-1 β-tubulin single nucleotide polymorphisms frequency between age groups, and no genetic evidence of reversion to benzimidazole susceptibility, despite targeted benzimidazole usage. This study highlights the need to include speciation when investigating gastrointestinal nematode epidemiology and anthelmintic resistance, and serves as an example of how genetic data may be analysed alongside species diversity and faecal egg counts, when markers for other anthelmintic classes are identified.